2017
DOI: 10.1002/cne.24279
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and stereological characterization of Hdc KO mice: Relation to Tourette syndrome

Abstract: A premature termination codon in the human histidine decarboxylase (Hdc) gene has been identified in a family suffering from Guilles de la Tourette syndrome (GTS). In the current study we investigated if mice lacking the histamine producing enzyme HDC share the morphological and cytological phenotype with GTS patients by using magnetic resonance (MRI) and diffusion tensor imaging (DTI), unbiased stereology and immunohistochemistry. Behavior of Hdc knock-out (Hdc KO) mice was assessed in an open field test. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…The striatum is the main input nucleus of the basal ganglia, which exhibits extensive modulation by histamine in adulthood (Doreulee et al, 2001;Ellender et al, 2011;Castellan Baldan et al, 2014;Bolam and Ellender, 2016;Rapanelli et al, 2017a), and much evidence points to alterations in cortico-striatal-thalamo-cortical loops in Tourette's syndrome (Felling and Singer, 2011;McNaught and Mink, 2011). A series of in vivo studies using mice with reduced brain histamine levels, either through gene KO (Castellan Baldan et al, 2014;Abdurakhmanova et al, 2017) or acutely through chemogenetic manipulation of histaminergic neurons (Rapanelli et al, 2017a,b), have shown that this can recapitulate some key symptoms (e.g., increases in repetitive behaviors) as a result of changes in striatum. However, these studies were focused on adult animals, which limits our understanding of histamine's role during early striatal development as well as in relation to neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The striatum is the main input nucleus of the basal ganglia, which exhibits extensive modulation by histamine in adulthood (Doreulee et al, 2001;Ellender et al, 2011;Castellan Baldan et al, 2014;Bolam and Ellender, 2016;Rapanelli et al, 2017a), and much evidence points to alterations in cortico-striatal-thalamo-cortical loops in Tourette's syndrome (Felling and Singer, 2011;McNaught and Mink, 2011). A series of in vivo studies using mice with reduced brain histamine levels, either through gene KO (Castellan Baldan et al, 2014;Abdurakhmanova et al, 2017) or acutely through chemogenetic manipulation of histaminergic neurons (Rapanelli et al, 2017a,b), have shown that this can recapitulate some key symptoms (e.g., increases in repetitive behaviors) as a result of changes in striatum. However, these studies were focused on adult animals, which limits our understanding of histamine's role during early striatal development as well as in relation to neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, standard open field test actually measures forced exploratory activity and represents the net result of two competing behavioral programs: exploration and stress‐induced defensive behavior . Previously we found no indication of increased anxiety in the novel open field in Hdc KO mice and in this study blood corticosterone levels after open field test were similar in Hdc WT and KO mice, thus pointing against increased anxiety and stress in Hdc KO mice . In addition, histamine‐deficient mice displayed increased numbers of body/head/forepaw shakes, further indicating an increase in stereotypic behavior or behavioral complexity, rather than enhanced escape behavior.…”
Section: Discussionmentioning
confidence: 53%
“…Hrh3 is involved in differential modulation of mRNA levels of striatal opioids, dyorphin and enkephalin. 11,12 Open field behavior, including general locomotion and rearings of Hdc KO mice has been described previously, but results have been inconsistent 4,[13][14][15][16] (see Table S1). Stereotypic behavior in Hdc KO mice has been quantified previously after treatment with high amphetamine doses, which induced immobility and focused sniffing in animals.…”
mentioning
confidence: 85%
See 2 more Smart Citations